The Effectiveness of Pictorial Teaching Materials in English Language to Improve the Understanding of Mentally Retarded - Thamrin, Heriani; Sunardi, Sunardi; Supriyadi, Supriyadi (Angstrom Centre of Education, 2023)
The Effectiveness of Using Pictorial Teaching Materials in Class VII English Learning (Studies at SMPLB)